2004
DOI: 10.1124/jpet.103.060442
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Antioxidants Mimic the Effects of 1,4-Dihydropyridines on Neurotensin Receptor Function in PC3 Cells

Abstract: This study aimed to determine the mechanism(s) by which 1,4-dihydropyridine Ca 2ϩ channel blockers (DHPs) enhance the binding of neurotensin (NT) to prostate cancer PC3 cells and inhibit NT-induced inositol phosphate formation. Earlier work indicated that these effects, which involved the G proteincoupled NT receptor NTR1, were indirect and required cellular metabolism or architecture. At the micromolar concentrations used, DHPs can block voltage-sensitive and store-operated Ca 2ϩ channels, K ϩ channels, and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Since it is of interest to investigate the effect from different stimuli simultaneously or in a given sequence [45][46][47], the proposed microfluidic-based system could provide the possibility to apply different stimulation test solutions to a selected area of cells in a controllable manner, i.e., simultaneously or as a series of plugs in a given sequence without mechanically disturbing cells. Future studies will investigate both (i) the historical effects of having previously exposed the cell to other agonists, on any given response, being measured; and (ii) longer term effects due to the mechanical effects of flow (shear-stress) on stretch receptors within the CHO cell.…”
Section: Comparison Of Effects Of Different Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since it is of interest to investigate the effect from different stimuli simultaneously or in a given sequence [45][46][47], the proposed microfluidic-based system could provide the possibility to apply different stimulation test solutions to a selected area of cells in a controllable manner, i.e., simultaneously or as a series of plugs in a given sequence without mechanically disturbing cells. Future studies will investigate both (i) the historical effects of having previously exposed the cell to other agonists, on any given response, being measured; and (ii) longer term effects due to the mechanical effects of flow (shear-stress) on stretch receptors within the CHO cell.…”
Section: Comparison Of Effects Of Different Agonistsmentioning
confidence: 99%
“…It can be seen that both curves show a similar trend, except that the UTP gave a stronger stimulation than ionomycin. It has been reported that UTP could induce calcium flux responses similar to ionomycin [45] although the cellular reaction mechanism was thought to be different [46].…”
Section: Comparison Of Effects Of Different Agonistsmentioning
confidence: 99%
“…One characteristic of the safrole-induced Ca 2+ entry is its insensitivity to voltage-gated Ca 2+ entry blockers. In PC3 cells, micromolar concentrations of dihydropyridines have been shown to block voltage-sensitive and store-operated Ca 2+ channels (35).…”
Section: Discussionmentioning
confidence: 99%
“…To increase the efficacy of anticancer drug and to reduce the toxic effect, a polymeric misceller and liposome based delivery system conjugated to tumor specific ligands have been studied 51 , 52 , 53 . In prostatic tumor -the tumor cell overexpress transferring receptor and for targeting drug to tumor, ligand transferring has been investigated 54 . For the treatment of a localize prostatic tumor the approach is direct intertumoral delivery of biodegradable nanoparticles, a controlled release formulation, providing sustained drug effect 55 .…”
Section: Nanodevices and Categories Of Nanomedicinementioning
confidence: 99%